Epidemiology of chronic thromboembolic pulmonary hypertension in Korea: results from the Korean registry - Park, So Young; Lee, Sang Min; Shin, Jong Wook; Choi, Byoung Whui; Kim, Hojoong; Lee, Jae Seung; Lee, Sang Do; Park, Sung Soo; Moon, Hwa Sik; Park, Yong Bum (The Korean journal of internal medicine, 2016)
The diagnosis of chronic thromboembolic pulmonary hypertension (CTEPH) is difficult for numerous reasons and is related with a poor prognosis. In Korea, the incidence of CTEPH and its clinical features are unknown. Thus, in this study, we evaluated the clinical characteristics and outcomes of CTEPH in a Korean cohort. This study included South Korean patients diagnosed with CTEPH between September 2008 and October 2011. Baseline characteristics, treatments and outcomes were analyzed. A total of 134 patients were included in this study with 76 females (56.7%). Their median age was 58.3 ± 15.9 years and dyspnea (112 patients, 83.5%) was the most common presenting symptom. Sixty-three patients (47%) had a history of acute pulmonary embolism or deep vein thrombosis, and six (4.5%) had pulmonary tuberculosis. In total, 28 patients (21%) underwent pulmonary thromboendarterectomy (PTE), and 99 patients had medical therapy. During the study period, 18 patients (13.4%) died. In a multivariate analysis, higher hemoglobin (relative risk [RR], 1.516; 95% confidence interval [CI], 1.053 to 2.184; p = 0.025) and lower total cholesterol levels (RR, 0.982; 95% CI, 0.965 to 0.999; p = 0.037) were associated with increased mortality. This was the first national cohort study of Korean patients with CTEPH. Accurate diagnosis, characterization and distributions of CTEPH are imperative for prompt treatment in patients, particularly those undergoing PTE.